Application of quadrupole-Orbitrap high-resolution mass spectrometry in rapid screening and identification of synthetic dyes in herbal medicines. Issue 5 (October 2019) - Guo, Changchuan; Li, Ke; Xing, Sheng; Sun, Hua; Shi, Feng; Zhang, Guifang; Sun, Haiyan
In this work, a method combining ultra-high performance liquid chromatography and hybrid quadrupole-Orbitrap high-resolution mass spectrometry (HR-MS) was developed and validated for use in the simultaneous screening, identification, and quantification of 21 synthetic dyes in herbal medicines. To optimize the chromatographic conditions, we used a combined Full mass scan and data-dependent MS/MS (Full MS/dd-MS 2 ) approach in positive and negative ion mode. Under this mode, selected ions with given fragmentation energy were subjected to a dd-MS 2 scan following a Full MS scan. The selectivity of this method was effectively improved using 70, 000 full width at half maximum mass resolution and narrow mass window (typically 5 ppm), and a single injection was sufficient for simultaneous identification and quantification of 21 synthetic dyes within 10 min. The combined method was fully validated and complies with all criteria for selectivity, sensitivity, calibration curve linearity, accuracy, precision, recovery, matrix effect, and stability. All analytes showed excellent linear relationships as all the coefficients of determination ( r 2 ) are greater than 0.9978 over wide ranges of concentrations (e.g. 1.0–500 ng/mL for sunset yellow). The validated method was employed to detect synthetic dyes in herbal medicines and was demonstrated to provide a reliable technical basis for drug regulation and public health protection.